Intensity-modulated proton beam therapy (IMPT) versus intensity-modulated photon therapy (IMRT) for patients with oropharynx cancer – A case matched analysis. Issue 1 (July 2016) - Blanchard, Pierre; Garden, Adam S.; Gunn, G. Brandon; Rosenthal, David I.; Morrison, William H.; Hernandez, Mike; Crutison, Joseph; Lee, Jack J.; Ye, Rong; Fuller, C. David; Mohamed, Abdallah S.R.; Hutcheson, Kate A.; et al.
Abstract: Background: Owing to its physical properties, intensity-modulated proton therapy (IMPT) used for patients with oropharyngeal carcinoma has the ability to reduce the dose to organs at risk compared to intensity-modulated radiotherapy (IMRT) while maintaining adequate tumor coverage. Our aim was to compare the clinical outcomes of these two treatment modalities. Methods: We performed a 1:2 matching of IMPT to IMRT patients. Our study cohort consisted of IMPT patients from a prospective quality of life study and consecutive IMRT patients treated at a single institution during the period 2010–2014. Patients were matched on unilateral/bilateral treatment, disease site, human papillomavirus status, T and N status, smoking status, and receipt of concomitant chemotherapy. Survival analyzes were performed using a Cox model and binary toxicity endpoints using a logistic regression analysis. Results: Fifty IMPT and 100 IMRT patients were included. The median follow-up time was 32 months. There were no imbalances in patient/tumor characteristics except for age (mean age 56.8 years for IMRT patients and 61.1 years for IMPT patients, p -value = 0.010). Statistically significant differences were not observed in overall survival (hazard ratio (HR) = 0.55; 95% confidence interval (CI): 0.12–2.50, p -value = 0.44) or in progression-free survival (HR = 1.02; 95% CI: 0.41–2.54; p -value = 0.96). The age-adjusted odds ratio (OR) for the presence of a gastrostomy (G)-tube during treatment for IMPT vs IMRT were OR = 0.53; 95% CI: 0.24–1.15; p -value = 0.11 and OR = 0.43; 95% CI: 0.16–1.17; p -value = 0.10 at 3 months after treatment. When considering the pre-planned composite endpoint of grade 3 weight loss or G-tube presence, the ORs were OR = 0.44; 95% CI: 0.19–1.0; p -value = 0.05 at 3 months after treatment and OR = 0.23; 95% CI: 0.07–0.73; p -value = 0.01 at 1 year after treatment. Conclusion: Our results suggest that IMPT is associated with reduced rates of feeding tube dependency and severe weight loss without jeopardizing outcome. Prospective multicenter randomized trials are needed to validate such findings.